TREATMENT OUTCOMES OF PHARMACOLOGICAL CLOSURE OF PATENT DUCTUS ARTERIOSUS IN PRETERM INFANTS UNDER 34 WEEKS OF GESTATION AT THE VIETNAM NATIONAL CHILDREN’S HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate treatment outcomes and analyze factors associated with pharmacological closure of patent ductus arteriosus in preterm infants under 34 weeks of gestation at the Neonatal Center, National Children’s Hospital during 2024-2025.Methods: A descriptive cross-sectional study was conducted on 190 preterm infants under 34 weeks’ gestation diagnosed with patent ductus arteriosus and treated at the Neonatal Center, National Children’s Hospital. Demographic data, clinical characteristics, treatment outcomes, and related factors were collected and analyzed.Results: The male-to-female ratio was 1.5:1. The 28-32 week age group accounted for the largest proportion (57.9%). Low birth weight (< 1500 gr) was found in 74.7% of infants. The most common age at treatment initiation was 3-7 days (60%). The rates of ductal closure after 3 and 6 days of treatment were 43.2% and 71.6%, respectively. Ibuprofen demonstrated a higher closure rate than Paracetamol, with ductal closure on day 6 reaching 82.8% compared with 66.7% (p = 0.035). The rate of ductal closure increased with gestational age; in infants under 28 weeks, closure rates after 3 and 6 days were 29.2% and 60%, while in those 32-34 weeks they were 66.7% and 80% (p < 0.05). Antenatal corticosteroid exposure was associated with a higher 6-day closure rate compared to the non-exposed group (77.8% vs. 64.8%, p = 0.048).Conclusion: Patent ductus arteriosus is commonly observed in preterm infants with gestational age under 32 weeks and low birth weight. Pharmacological closure using Ibuprofen or Paracetamol proved effective and helped reduce complications associated with patent ductus arteriosus.
Keywords: Newborns, premature, patent ductus arteriosus